2009
DOI: 10.1007/s10853-008-3237-2
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, structural characterisation and antibacterial properties of Ga-doped sol–gel phosphate-based glass

Abstract: A sol-gel preparation of Ga-doped phosphate-based glass with potential application in antimicrobial devices has been developed. Samples of composition (CaO) 0.30 (Na 2 O) 0.20-x (Ga 2 O 3 ) x (P 2 O 5 ) 0.50 where x = 0 and 0.03 were prepared, and the structure and properties of the gallium-doped sample compared with those of the sample containing no gallium. Analysis of the 31 P MAS NMR data demonstrated that addition of gallium to the sol-gel reaction increases the connectivity of the phosphate network at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 38 publications
2
31
0
Order By: Relevance
“…Therefore, gallium inhibits Fe 3+ biological functions by a “Trojan horse” strategy . This strategy can be exploited to interfere with or disrupt the iron metabolism in a large number of bacterial strains, including P. aeruginosa , Mycobacteria , Clostridium difficile , and the methicillin‐resistant S. aureus …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, gallium inhibits Fe 3+ biological functions by a “Trojan horse” strategy . This strategy can be exploited to interfere with or disrupt the iron metabolism in a large number of bacterial strains, including P. aeruginosa , Mycobacteria , Clostridium difficile , and the methicillin‐resistant S. aureus …”
Section: Discussionmentioning
confidence: 99%
“…Recently, several inorganic antimicrobial agents have been used as a promising strategy to discourage biofilm formation onto implant surfaces by exploiting their known antibacterial properties to reduce both the systemic antibiotic therapy and the surgical procedures necessary to remove the infected implants . In particular silver (Ag) and gallium (Ga), a semimetallic element in group 13 (3 + ), have been shown to be effective in the prevention of implant surgical infections . Bacteriostatic/bactericide properties of silver are well known and are mainly due to its multiform mechanisms to damage bacteria even at very low concentrations .…”
Section: Introductionmentioning
confidence: 99%
“…Pickup et al . 25 investigated the antibacterial activities of a Ga‐doped sol‐gel PBGs of composition (CaO) 0.30 (Na 2 O) 0.20‐ x (Ga 2 O 3 ) x (P 2 O 5 ) 0.50 where x = 0 and 0.03 mol %. They observed a small zone of inhibition (7 mm) for the gallium‐free glass and they attributed it to either a change in pH as the glass dissolves or by reduced water activity as ions leach out.…”
Section: Discussionmentioning
confidence: 99%
“…Doping bioactive glass with other ions, such as yttrium, selenium, and iodine also show potential for antimicrobial activity [21] [24]. Gallium doped sol-gel phosphatebased glasses have also shown promising antimicrobial activity against S. aureus and Streptococcus mutans [27] and phosphate based glasses doped with both silver and gallium have been shown to be effective against P. aeruginosa biofilm formation [25].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies have revealed that antimicrobial effects of gallium are likely intracellular and involve disruption of bacterial iron uptake [27] [28].…”
Section: Introductionmentioning
confidence: 99%